Catalytic conversion of RBD palm oil to fuel : the effect of silica-alumina ratio in ZSM-5 - Mohd Qamaruddin, Ahmad (2009)
The refined, bleached and deodorized (RBD) palm oil was converted to Organic Liquid Products (OLP) by passing it’s the vapor through ZSM-5 catalyst. The constituents of OLP consist of gasoline, C12-C15, and other type of organic liquid. The equipment that was used to carry out the experiment was modified based on the suitability of the substance used. There are three types of ZSM-5 that were used to investigate the effect of ratio of silica oxide to the alumina oxide (23 SiO2/Al2O3). From recent research has showed that zeolite ZSM-5 with the ratio of 23 SiO2/Al2O3 will produce the highest OLP amount in which are about 96.9%. The alumina oxide in ZSM-5 is the one that influences the strength of the acid site zeolite. Therefore, the relationship between the two is inversely proportional, which when the ratio is lower, the higher the strength of the acid will be. The ratio of 23 SiO3/Al2O3 is the smallest ratio when compared to the other three catalysts than were used. The rate of conversion of palm oil to OLP is influenced by the concentration of acid site. All the OLP was analyzed with Fourier Transform Infrared (FTIR) in order to detect the functional group of alkanes, alkenes and aromatic. The products was analyzed and shown that the functional groups is presence, which showed that all the ratio that was used can convert palm oil to OLP.